Embrittlement mechanism of 460 MPa-Grade nuclear power steel deposited after heat treatment. (April 2023) - Zuo, Yue; An, Tongbang; Ma, Chengyong; Kang, Ju
Abstract: The effects of post-welded heat treatment on microstructure evolution and embrittlement mechanism of 460 MPa-grade nuclear power steel deposited metal were studied using optical microscope, scanning electron microscope, transmission electron microscope and electron backscattered diffraction (EBSD). The results showed that there was no significant change in the type of deposited metal microstructure before and after heat treatment, except for some acicular ferrite turning into block ferrite. Further studies showed that the dispersive martensite-austenite (M-A) constituent did not worsen the toughness of the deposited metal. However, after heat treatment, the M-A constituent decomposed into ferrite and carbides, where the carbides were precipitated on the grain boundary, resulting in grain boundary embrittlement. The precipitated carbides also increased the dislocation tangle on the grain boundary, which was prone to causing stress concentration and induced crack initiation, resulting in the cleavage fracture. The analysis of the orientation characteristics of the impact fracture profile via EBSD showed that the ferrite laths were coarsened and the high-angle grain boundaries were reduced after heat treatment. Meanwhile, the plastic crack propagation was terminated earlier resulting in the early initiation of cleavage fracture. Moreover, the crack propagation path was smooth and secondary cracks formed during the propagation process. Finally, after heat treatment the inclusions easily fell off and formed micro-voids, which provided favorable channels for crack propagation and accelerated the deterioration of impact toughness. All of these were factors for the significant decline in the toughness of the heat-treated deposited metal. Highlights: The effect of M-A constituent and its decomposition on the impact toughness of the deposited metal was studied. The influence of grain and grain boundary changes before and after heat treatment on impact toughness was analyzed. The embrittlement mechanism for the deposited metal of 460 MPa-grade nuclear power steel was proposed.